Antenatal care practice and pregnancy out come at Sikuati area, Kudat, Sabah - Tin, Tin Aye; Datuk Yusof Ibrahim; Daw, Khin Saw Naing; Than Myint; Muhammad Hj Jical (Universiti Malaysia Sabah, 2016)
Antenatal (AN) care is vital for all pregnant women and for reduction of maternal mortality and morbidity. AN care knowledge and specific AN care practices are some of the crucial components of what determines effective AN care. In developing nations, the health of pregnant women can be even more sensitive to these factors. Objectives of this study was to assess the antenatal ( AN) care practice and pregnancy outcome of ever-married women aged 18 to 49 years old having at least one pregnancy experience, residing in kampongs of Sikuati area, Kudat between March to December 2015. Cross–sectional descriptive study, non-probability convenient sampling method was used and 150 eligible participants were interviewed through face to face by trained interviewers using a semi- structured questionnaire and their knowledge of AN care, their AN care practices and outcomes and complications of their pregnancies were recorded. 99% of all the women received AN care, and 64% of the women received essential AN care practice (AN visit of minimum 4 times). The study revealed that overall knowledge amongst the women with good knowledge was 48% and low knowledge was 52%. Despite this, it was found that low knowledge of AN care was associated with essential AN care practice. Additionally, AN care practices, assessed through timing of first AN care visit and frequency of visits, was not significantly associated with pregnancy complications. Despite these results, outcomes were good and all complications were properly and successfully addressed. This may reflect the effectiveness of current programs in place promoting importance of AN care and delivery practices. Maintenance of current programs with targeted interventions to address low knowledge level and the low level of compliance with essential AN care completed are recommended.